Working mother’s awareness and practice regarding feeding of expressed breast milk (Journal of Patan Academy of Health Sciences, 2019)
Introductions: Expressed breast milk (EBM) is a healthy feeding option as compared to formula milk for working mothers. Awareness and practice towards EBM may be helpful towards its promotion. Methods: A cross sectional study was conducted at Patan Hospital, Patan Academy of Health Sciences, Nepal. Working mothers with breastfeeding child of less than 2 year were interviewed for and practice regarding EBM. A self-constructed open and close ended questionnaire in Nepali was used for data collection to analyze the association of mother’s age, types of family structure and number of children with EBM. Results: Out of 178 working mothers, 121 (67.9%) had awareness about EBM and 22 had practiced it. Mother’s age, types of family structure and number of children were not statistically significant with level awareness. There was positive correlation between awareness and practice of EBM. Conclusions: This study demonstrated 2/3rd of working mothers had awareness of EBM and 1/10th practiced EBM feeding, and there was positive correlation of awareness and practice.